Credit Booms Gone Bust: Monetary Policy, Leverage Cycles, and Financial Crises, 1870–—2008 - Schularick, Moritz; Taylor, Alan M. (The American economic review, 2012)
The financial crisis has refocused attention on money and credit fluctuations, financial crises, and policy responses. We study the behavior of money, credit, and macroeconomic indicators over the long run based on a new historical dataset for 14 countries over the years 1870–2008. Total credit has increased strongly relative to output and money in the second half of the twentieth century. Monetary policy responses to financial crises have also been more aggressive, but the output costs of crises have remained large. Credit growth is a powerful predictor of financial crises, suggesting that policymakers ignore credit at their peril. JEL: E32, E44, E52, G01, N10, N20